The colon cancer screening behaviours survey for South Asians: a pilot study of feasibility and psychometric evaluation - Joanne Crawford; Frederick Morfaw; Farah Ahmad; Lehana Thabane; Angela Frisina (SpringerOpen, 2020)
Abstract Purpose The purpose of the study was to pilot test the English and Urdu version of the Colon Cancer Screening Behaviours Survey among South Asians in Canada. The first objective was to evaluate feasibility of administration, data collection using computer assisted personal interviewing software on a tablet, and response burden. The second objective was to examine the prevalence of colorectal cancer screening among South Asians and evaluate the psychometric properties of sub-scales in the survey. Methods Purposive, network and snowball sampling were used to recruit participants for this cross-sectional study. Interviewer-led administration of the Colon Cancer Screening Behaviours Survey was conducted across two cities in Ontario, Canada. Qualitative data analysis assessed feasibility; and sub-scales were evaluated through principal component analysis, item-scale correlations, and construct validity using multiple linear and logistic regression. Results A total of 328 South Asians participated, 47% Urdu speaking, and 53% English speaking. There was a 23% refusal rate to participate. Feasibility identified: (1) successful recruitment despite reasons for refusal; (2) problematic items and response categories; and (3) computer/tablet limitations. Principal component analysis identified 14 components that explained 68.7% of total variance; 34 items were retained after factor analysis. Internal consistency of 4 scales ranged from 0.79-0.91. There were significant differences in perceived barriers scale scores (− 12.21; 95% CI, − 17.13 to - 7.28; p <  0.0001) between those who participated and those who did not participate in screening. No association was found with years of residence and uptake of screening after adjustment (OR 0.91 (0.46-1.79), p = 0.783). Conclusions Recruitment and data collection methods are feasible among South Asians if functionality of the tablet selected is improved. The Colon Cancer Screening Behaviours Survey was finalized and retained items in sub-scales demonstrated good psychometric properties to assess behaviours for colon cancer screening among South Asians in Canada. The interviewer-led survey may be used by public health, cancer care or other health practitioners to describe or predict colorectal cancer screening behaviours among South Asians in similar settings or adapted and tested in other contexts.